Moisès Broggi i Vallès (1908–2012): Military surgeon and Catalan humanitarian. (February 2016) - Derby, Mark; Jorge, David
Catalan surgeon Moisès Broggi entered medical practice in 1931 as Spain was modernizing rapidly. Five years later, however, an attempted military coup sparked a nationwide civil war. Broggi offered his services to the embattled Republic and joined the Medical Service of the International Brigades. He served alongside colleagues from many countries, helping to develop advances in military medicine and especially trauma surgery. Broggi chose to remain working in Barcelona as Franco's Nationalist forces entered the city, in spite of the risk of reprisal he faced as a former officer of the International Brigades. Although forced from his leading position in the public health service, he developed a distinguished private practice. In the year of Franco's death he became President of Barcelona's Royal Academy of Medicine and he received many other honours. Just months before his death at the remarkable age of 104, Dr Moisès Broggi continued to discuss and write about the concerns that had directed the course of his life – advances in medical science and the intellectual and political repression that had hindered delivery of those advances. In an article titled Exile and Silence he noted the groundbreaking work carried out under the auspices of the prestigious scientific institutions founded during Spain's Second Republic and the subsequent dark decades of exile suffered by many of their prominent scientists, some of them his close friends.